UMAH LAHIEK KERINCI SEBAGAI IDE DALAM PENCIPTAAN KARYA SENI LUKIS - Acel Alfatomi; Awerman Awerman; Dharsono soni kartika (Ranah Seni, 2018)
Abstrac The creation of a painting with the theme "umah lahiek kerinci as a painting art idea" is a painting inspired by a traditional house of kerinci district, commonly called kerinci tribe house. Umah lahiek is a traditional residential house of kerinci tribe society which has a long lined pattern of connecting between one house and the house beside it. The pattern of umah lahiek as a long house is divided into several plots inhabited by one batih family (batik in the sense of husband and wife and their children), the order of this batik family according to the belly system, kelebu, tumbi. It means that in the social life of their families and their rabbits together, they have lived together in harmony, peace, mutual peace, mutual trust and respect between them, the rabid community has a strong sense of religion and kinship and fanaticism of customs, kerinci can also survive with the nature of his instincts, namely honest, obedient, helpful help, a very prominent sense of brotherhood and kinship, which can be seen when they work on rice fields and build homes. The interest in kerinci's home is to express ideas of aspiration to work in painting using the concept of reinterprestation and also to apply important social values in the daily life of kerinci community. And also the legacy that should be preserved and developed. The social life of the people who inhabited the house was touching the artist's heart to create a work of art. Because, this work of art not only to convey the message but to apply the values of humanity in the past through artwork.